Characteristics of Adult Celiac Disease in Eastern Algeria - Nousseiba Abed; Imen Bouzaroura; Amel Guergour (Journal of Biomedical & Clinical Research)
The objective of this study was to determine the clinical picture of adult celiac disease in the population of eastern Algeria. We conducted a retrospective study on a sample of 156 patients in Internal Medicine service, Hepato-Gastroenterology Service, Endoscopy Service in the University Hospital BENBADIS - Constantine and the Military Regional University Hospital - Constantine. Our results have shown that, in this population, celiac disease can be manifested by a number of signs and related pathologies. A variety of digestive symptoms were reported, primarily chronic diarrhea (81.4%), abdominal pain (57.1%), anorexia (42.9%) and vomiting (48%). Extra-digestive symptoms manifested mainly as weight loss (90.4%), pallorous of skin and mucosa (84%), asthenia (60,3%), edema of the lower limbs (46.8%) and dehydration sings (37.8%). In addition, we noted biological disorders, the most common being hypocalcemia (77.4%) and hypoalbuminemia (57.7%), and a series associated pathologies namely: anemia (67.9%) and digestive diseases (38.46%). CD in adults in our population may express a variety of digestive and extra-digestive symptoms in addition to a number of associated pathologies.